‘My Most Tricky Pickle!’ Balancing Reading Instruction in Play-Based Kindergarten: Educator Self-Efficacy Beliefs and Pedagogical Content Knowledge Needs - Messenger, Yvonne; Gallagher, Tiffany L. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2024)
Many kindergarten educators grapple with how best to teach reading in play-based kindergarten classrooms. The purpose of this mixed-methods study was to ascertain the instructional strengths and needs of kindergarten educators as they teach reading in play-based programs. Fifteen kindergarten teachers participated in an online questionnaire and focus group conversations that explored their concepts of self-efficacy and professional content knowledge to gain an understanding of the tensions these educators expressed, and to compare and confirm these with existing literature. Educators felt quite confident that they were effectively weaving foundational reading skills with learning opportunities into authentic experiences throughout the day. They indicated that balancing competing priorities within their programs was a challenge, and that supporting multilinguals and deepening their understanding of how to effectively build oral language and phonological awareness in their students were areas where they wanted to build their professional content knowledge.